Behaviour of 4‐ to 5‐year‐old nondisabled ELBW children: Outcomes following group‐based physiotherapy intervention. (28th July 2017) - Brown, L.; Burns, Y. R.; Watter, P.; Gray, P. H.; Gibbons, K. S.
Abstract: Background: Extreme prematurity or extremely low birth weight (ELBW) can adversely affect behaviour. Nondisabled ELBW children are at risk of behavioural problems, which may become a particular concern after commencement of formal education. This study explored the frequency of behavioural and emotional problems amongst nondisabled ELBW children at 4 to 5 years of age and whether intervention had a positive influence on behaviour. The relationship between behaviour, gender, and other areas of performance at 5 years was explored. Methods: Fifty 4‐year‐old children (born <28 weeks gestation or birth weight <1, 000 g) with minimal/mild motor impairment were randomly allocated to intervention ( n = 24) or standard care ( n = 26). Intervention was 6 group‐based physiotherapy weekly sessions and home programme. Standard care was best practice advice. The Child Behavior Checklist (CBCL) for preschool children was completed at baseline and at 1‐year post‐baseline. Other measures at follow‐up included Movement Assessment Battery for Children Second Edition, Beery Visual‐Motor Integration Test 5th Edition, and Peabody Picture Vocabulary Test 4th Edition. Results: The whole cohort improved on CBCL total problems score between baseline (mean 50.0, SD 11.1) and 1‐year follow‐up (mean 45.2, SD 10.3), p = .004. There were no significant differences between groups over time on CBCL internalizing, externalizing, or total problems scores. The intervention group showed a mean difference in total problems score of −3.8 (CI [1.5, 9.1]) between times, with standard care group values being −4.4 (CI [1.6, 7.1]). Males had higher total problems scores than females ( p = .026), although still performed within the "normal" range. CBCL scores did not correlate with other scores. Conclusions: The behaviour of nondisabled ELBW children was within the "normal" range at 4 to 5 years, and both intervention and standard care may have contributed to improved behavioural outcomes. Behaviour was not related to performance in other developmental domains.